Hemispheric Differences in Functional Interactions Between the Dorsal Lateral Prefrontal Cortex and Ipsilateral Motor Cortex - Wang, Yanqiu; Cao, Na; Lin, Yitong; Chen, Robert; Zhang, Jian (Frontiers in Human Neuroscience, 2020)
Background: The dorsolateral prefrontal cortex (DLPFC) in both hemispheres have a central integrative function for motor control and behavior. Understanding the hemispheric difference between DLPFC and ipsilateral motor cortex connection in the resting-state will provide fundamental knowledge to explain the different roles DLPFC play in motor behavior. Purpose: The current study tested the interactions between the ipsilateral DLPFC and primary motor cortex (M1) in each hemisphere at rest. We hypothesized that left DLPFC has greater inhibitory effect on the ipsilateral M1 compared to the right DLPFC. Methods: Fourteen right-handed subjects were tested in a dual-coil paired-pulse paradigm using transcranial magnetic stimulation. The conditioning stimulus (CS) was applied to the DLPFC and the test stimulus (TS) was applied to M1. Interstimulus intervals (ISIs) between CS and TS were 2, 4, 6, 8, 10, 15, 20, 25 and 30 ms. The result was expressed as a percentage of the mean peak-to-peak amplitude of the unconditioned test pulse. Results: There was stronger inhibitory effect for the left compared to the right hemisphere at ISIs of 2 (p = 0.45), 10 (p = 0.006), 15 (p = 0.029) and 20 (p = 0.024) ms. There was no significant inhibition or facilitation at any ISI in the right hemisphere. Conclusions: The two hemispheres have distinct DLPFC and M1 cortico-cortical connectivity at rest. Left hemisphere DLPFC is dominant in inhibiting ipsilateral M1.